2011
DOI: 10.4049/jimmunol.1100243
|View full text |Cite
|
Sign up to set email alerts
|

Human Bone Marrow Hosts Polyfunctional Memory CD4+ and CD8+ T Cells with Close Contact to IL-15–Producing Cells

Abstract: Recently, a key role in memory T cell homing and survival has been attributed to the bone marrow (BM) in mice. In the human BM, the repertoire, function, and survival niches of CD4+ and CD8+ T cells have not yet been elucidated. In this study, we demonstrate that CD4+ and CD8+ effector memory T cells accumulate in the human BM and are in a heightened activation state as revealed by CD69 expression. BM-resident memory T cells produce more IFN-γ and are frequently polyfunctional. Immunofluorescence analysis reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
110
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(122 citation statements)
references
References 54 publications
10
110
0
Order By: Relevance
“…27,28 A recent study suggests that this may also occur in humans. 29 Thus, BM is potentially a major source of these cells mobilized to the blood by plerixafor.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 A recent study suggests that this may also occur in humans. 29 Thus, BM is potentially a major source of these cells mobilized to the blood by plerixafor.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 Vaccination studies have identified effector memory T cells in mouse bone marrow that may serve as a reservoir, 32,33 and this may also be true in humans. 34 Thus, bone marrow is potentially a major source of all the major cell types mobilized to the blood by plerixafor. However, our serial biopsy/ aspirate data were most consistent with bone marrow being a source for neutrophil and B-cell mobilization, since the frequency of these 2 cell types declined from baseline after 6 months of plerixafor treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In mice, 30%‐40% of bone marrow CD8 + memory T cells express CD69,117 and about 40%‐50% of bone marrow CD4 + memory T cells 137. Expression of CD69 is induced upon activation of T cells138 and therefore has been conceived as a marker of activation, also for bone marrow memory T cells 133, 139. However, in murine bone marrow, neither CD69 + nor CD69 − memory CD4 + T cells are cycling according to Ki‐67 expression 137.…”
Section: The Lifestyle Of Bone Marrow Memory T Lymphocytesmentioning
confidence: 99%